EFEKTIVITAS PENDAYAGUNAAN DANA ZAKAT, INFAK DAN SEDEKAH (ZIS) PADA PROGRAM BANGKIT LAZ PERSIS KLP CIPEDES KOTA TASIKMALAYA - Muhamad Zainul Abidin; Jajang Rusmana (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2023)
This study aims to explain the effectiveness of the utilization of zakat, infaq and alms (ZIS) funds in the BANGKITLAZ Persis KLP Cipedes program. This program has not been carried out for a long time to cover the area of TasikmalayaCity where there are still many mustahik in Tasikmalaya City who need business capital assistance, so with this problemthe authors want to examine how effectively this program is running for increasing the welfare of mustahik in this casethose who have micro businesses located around Cipedes District according to the location where this program isimplemented.The research conducted is descriptive qualitative research, because according to the author this method issuitable and relevant to the object of research. In this study, the data used were qualitative data, namely those originatingfrom primary and secondary data which were then formulated and interpreted so that they were arranged into one. Datacollection was carried out using observation techniques, interviews, documentation, and literature study. All of theseinstruments support and complement each other in order to obtain complete and accurate data.The results showed that LAZ Persis KLP Cipedes had succeeded in utilizing zakat, infaq and alms funds inincreasing the welfare of mustahik with a total of 21 beneficiaries who were successfully empowered in the Rise program.The BANGKIT program has been running effectively as evidenced by the increase in the level of income earned by mustahikbefore and after receiving assistance. Then, there has also been an increase in the spiritual aspect of the mustahik whichis in accordance with the aim of the Rise program, namely to increase the spirituality of the recipients of venture capitalassistance